1999
DOI: 10.2165/00002018-199920020-00003
|View full text |Cite
|
Sign up to set email alerts
|

A Risk-Benefit Assessment of Anti-Obesity Drugs

Abstract: This review evaluates the benefits and potential health risks of the currently used drugs that are approved for the pharmacological treatment of obesity. Analysis of several long term clinical trials indicates that all of these drugs are efficient in reducing excess bodyweight, and that the majority of them allow the maintenance of the reduced bodyweight for at least 1 year. However, the loss of bodyweight attributable to these drugs is in general rather modest, approaching only 0.2 kg per week during the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 50 publications
0
18
0
3
Order By: Relevance
“…However, the mechanism for Orlistat, which is to inhibit pancreatic lipase, leads to the undesirable side effect of fecal leakage (15). An alternative approach may be to allow for the digestion of fat to fatty acids in the gut but block the uptake or the packaging of fatty acids into chylomicron particles.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism for Orlistat, which is to inhibit pancreatic lipase, leads to the undesirable side effect of fecal leakage (15). An alternative approach may be to allow for the digestion of fat to fatty acids in the gut but block the uptake or the packaging of fatty acids into chylomicron particles.…”
Section: Discussionmentioning
confidence: 99%
“…[158][159][160][161][162] Appetite-suppressing agents have lost favor due to their side effects. 163 Recent data suggest a role for orlistat, a lipase inhibitor, as an adjunct to weight loss. 164 Several studies have reported beneficial effects of bariatric surgery, [165][166][167] although precipitous weight loss has the potential to exacerbate steatohepatitis.…”
Section: Managementmentioning
confidence: 99%
“…However, these medications were found to have multiple, potentially fatal side effects, or a potential for abuse, which resulted in either their withdrawal from the market, or to the implementation of regulations prohibiting their use in the treatment of obesity 21,22 . The most recent prescription anti-obesity medications to be removed from the market were fenfluramine and its isomer dexfenfluramine.…”
Section: Previous Therapymentioning
confidence: 99%